CURRENCY AS A TOOL BONDS OF LOCAL BORROWING - І. Liuty; K. Kuryshchuk (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The article expediency diversification tool for local government borrowing through further improvement of circulation of government bonds denominated in foreign currency, with an emphasis on intensifying their placement among the population. The influence of foreign bonds to the efficient management of foreign currency liquidity of commercial banks in Ukraine.